2022
DOI: 10.2807/1560-7917.es.2022.27.32.2101096
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection in households with and without young children: Nationwide cohort study, Denmark, 27 February 2020 to 26 February 2021

Abstract: Background Infections with seasonally spreading coronaviruses are common among young children during winter months in the northern hemisphere; the immunological response lasts around a year. However, it is not clear if living with young children changes the risk of SARS-CoV-2 infection among adults. Aim Our aim was to investigate the association between living in a household with younger children and the risk of SARS-CoV-2 in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several studies have reported an increased risk of infection for the members of households with children. 20 , 21 , 22 , 23 , 24 Measuring the risk of infection for members of households with children can identify associations regardless of the likelihood of the child being tested and changes in school testing policies, but these associations can evolve following changes in vaccine coverage, the strains circulating in the population, and the interventions focusing on children. We used this approach in the ComCor case-control study, 25 , 26 further analyses of which are presented here.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported an increased risk of infection for the members of households with children. 20 , 21 , 22 , 23 , 24 Measuring the risk of infection for members of households with children can identify associations regardless of the likelihood of the child being tested and changes in school testing policies, but these associations can evolve following changes in vaccine coverage, the strains circulating in the population, and the interventions focusing on children. We used this approach in the ComCor case-control study, 25 , 26 further analyses of which are presented here.…”
Section: Introductionmentioning
confidence: 99%